Penggugatan Hak Kekayaan Intelektual Pada Merek Dagang Ps Glow Milik Putra Siregar - Apriliana Dwi Harwanti; Adhiya Faisal; Davina Kheisya Alliyah Gumay; Dwi Desi Yayi Tarina (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Intellectual Property Rights Disputes are problems that often arise in the world of trade, one of which is regarding trademark rights. Brands have a very crucial role in running a business efficiently and in supporting healthy business competition. This is due to the fact that a brand acts as an identifying mark for a particular product, allowing customers to recognize and differentiate the quality of the goods or services they consume. This research discusses a brand problem between MS GLOW and PS GLOW which went viral some time ago where the brands were involved in a brand plagiarism dispute. This research examines from a juridical perspective how to resolve Intellectual Property Rights disputes, as well as the process of resolving brand plagiarism in the PS GLOW case owned by Putra Siregar which resembles the MS GLOW brand owned by Shandy Purnamasari. This research was conducted based on legal principles, legal methods, legal structures, and regulations relevant to the issues discussed in this journal. Disputes regarding Intellectual Property Rights can be carried out through litigation and non-litigation. The settlement of the case between MS GLOW and PS GLOW was carried out through litigation and has resulted in a decision that has permanent legal force. The results of this research reveal that MS GLOW succeeded in winning the case at the Medan Commercial Court, because Shandy Purnamasari was the first person to use and register the MS GLOW brand at the Intellectual Property Department. The judge's consideration stated that MS GLOW was the only product brand that was first registered with the Directorate General of Intellectual Property (Ditjen KI), and that PS GLOW had fundamental similarities with MS GLOW. Intellectual Property Rights, MS Glow, PS Glow